Older adults’ perceptions about methodologies used to learn English as a foreign language - Cecilia Cisterna Zenteno; Marcela Cabrera Abarza; Ignacio Roa Herrera (Cuadernos de Investigación Educativa, 2025)
Older adults' increased longevity and improved health are becoming a great achievement in this century. In lifelong learning, active learners in the community benefit from a variety of courses offered by different institutions, with foreign language learning showing particular positive effects on emotional and mental health. Teaching a foreign language to older adults requires teachers to use specific approaches and effective strategies. The main aim of the following study was to analyze older adults' perceptions of the teaching methodologies for learning English in terms of activity types, resources, approaches, and motivations to learn the language. A convenience sample of 24 participants who attended English classes at a Chilean university was selected. This descriptive-quantitative study collected data using a Likert scale survey, highlighting key trends and patterns derived from participants' experiences in a shared educational setting. Data analysis included measures of central tendency and word cloud analysis. The results showed that older adult learners appreciate socially interactive English lessons that involve sharing experiences; they enjoy using audiovisual resources but find listening and reading skills challenging due to limited vocabulary and age-related hearing impairments.